Analysis Of Marketing Mix Strategy At Ayam Gepuk Pak Gembus Jatinangor Sumedang - Teguh Suhara; Ucu Supriatna (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the implementation of the Marketing Mix (7P) strategy at Ayam Gepuk Pak Gembus Jatinangor Branch. The research employed a qualitative approach using interviews, observation, and documentation as data collection techniques. Informants consisted of the owner, employees, and customers. The results indicate that the main product is crushed fried chicken with adjustable spiciness levels, although menu variations remain limited. The prices range from Rp15,000 to Rp20,000 and are considered affordable for students. The business location is strategic, being near university areas, but has limited parking space. Promotional activities depend largely on headquarters and online delivery applications. Employee service is generally good, although some customers perceive it as less friendly. The service process is simple and efficient; however, queues increase during peak hours. Physical evidence such as cleanliness, comfort, and packaging supports positive customer perceptions. It can be concluded that the 7P marketing mix strategy is relatively effective in attracting customers, yet improvements in product variety, independent promotion, and service consistency are needed.